The mediating role of learning motivation in the relationship between the ials module and speaking performance among Chinese EFL undergraduates: A proposal - Yi Yang; Asmaa AlSaqqaf (Human Resource Management Academic Research Society (HRMARS), 2024)
Chinese EFL undergraduates encounter significant obstacles in acquiring spoken English. This challenge is partially attributed to affective factors, notably learning motivation, which holds a crucial role in the language learning process. Regrettably, Chinese undergraduates often exhibit a dearth of motivation in developing their speaking abilities, as speaking skills are typically marginalized within the national assessment. Autonomous learning and incentive strategies as two vital factors influencing students’ learning motivation and speaking performance, are integrated to form the Incentive Autonomous Learning Strategies (IALS) Module. Based on the literature review, studies exploring the interrelationship among the IALS module, learning motivation, and speaking performance remain scarce. Consequently, this paper attempts to conceptualize the association between the IALS module and students' speaking performance, mediated by learning motivation at a public university in China. Adopting a quantitative approach, this study utilizes a correlation research design with a purposive sampling, where 42 participants are administered a learning motivation questionnaire (mediator), an incentive strategies questionnaire (independent variable), and given a speaking test (dependent variable), while linear regression is deployed to analyze their relationships. It is hoped that the study may contribute valuable insights into the interplay of the developed module, learning motivation, and speaking competence.